Seasonal histomorphological studies on the thyrotrophs of Gaddi sheep - PARAMASIVAN, S; SHARMA, D N (The Indian Journal of Animal Sciences, 2014)
The cytoplasm i.e. granules of large, round or polyhedral TSH cells stained mildly or intensely with aniline blue, periodic acid Schiff and Gomori's aldehyde fuchsin stains. The number of thyrotrophs increased significantly during winter (210±12.74 cells/mm2) when compared with summer (126±12.24 cells/mm2). The average diameter of TSH-cells varied from 9.14±0.1l um during winter to 8.35±0.20 um during summer. Its nucleus measured 4.59±0.09 um during summer but enlarged to 4.86±0.08 um during winter. This physiological increase in size of the TSH cell and their population during winter might be associated with the increased BMR.